Correlation Between Gratitude and Social Comparison with Body Image in Vocational High School (SMK) Students - Della Tri Damayamti; Ahmad Saifuddin (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2022)
This study aimed to determine the correlation between gratitude and social comparison with body image in adolescents. This research used a quantitative approach with the correlation study involving 136 students of the Online Marketing and Business Expertise Program at SMK Negeri 3 Surakarta, female students aged 15-18 years. Data were collected using a measuring instrument for gratitude using the concept of Al Ghazali, a measuring instrument for social comparison using the theory of Jones, and a measuring instrument for body image using the theory of Cash & Pruzinsky. This study used content validity by involving seven experts or raters. The results showed that gratitude had a reliability coefficient of 0.917, the social comparison had a reliability coefficient of 0.913, and body image had a reliability coefficient of 0.883. Based on hypothesis testing using multiple regression analysis, the results showed that gratitude and social comparison simultaneously had a significant correlation with body image, with a correlation coefficient of 0.192 and a significance value of 0.000 (p <0.05). Then partially, gratitude had a positive correlation with body image, with a correlation coefficient of 0.425 with a significance value of 0.001 (p <0.05). Meanwhile, the social comparison had no correlation with body image because it had a correlation coefficient of -0.342 with a significance value of 0.178 (p>0.05).